CHAPTER 17: Effect of Fluoride on the Sensitivity and Secretion of Insulin - Lombarte, Mercedes; Rigalli, Alfredo; Chiba, Fernando Yamamoto [UNESP]; Sumida, Doris Hissako [UNESP] (Royal Society of Chemistry (RSC), 2015)
Fluoride has been used in the treatment of osteoporosis and in the prevention of dental caries. However, excessive fluoride intake causes significant systemic alterations in animals and human beings. In this chapter disturbances induced in glucose homeostasis are discussed: hyperglycemia, impaired glucose tolerance and modification of metabolic pathways of glucose and glycogen. These changes are the consequence of an inhibition of insulin secretion and/or a reduction in insulin sensitivity.